EDUCATION - THE FOUNDATION FOR SUSTAINABLE ECONOMIC DEVELOPMENT. THE „RESPECT” LEARNING STRATEGY PRINCIPLES IMPLEMENTED IN HIGHER ECONOMIC EDUCATION - MINICA, Mirela (Ecoforum Journal, 2016)
The present article highlights exactly these principles of human capital and economic development and the concept of learning strategy, as representing the initial stage of an educational project that proposes a scientific approach based on designing, experimenting, validating and drafting a learning model in the field of economic sciences.